Assessing the value of enrofloxacin and carprofen combination treatment in southern white rhinoceros (Ceratotherium simum) through the use of pharmacokinetic modelling - Naidoo, Vinny (University of Pretoria, 2018)
Over the past decade, the poaching of white rhinoceros (Ceratotherium simum) has increased dramatically. More than 7000 animals have been killed and approximately 200 animals annually survive the poaching attempts with life threatening injuries, which require immediate medical attention. Despite their need for veterinary care, knowledge on the treatment of white rhinoceros is scarce. Approved drugs are non-existent and dosages need to be extrapolated arbitrarily from other species. In order to successfully treat injured poaching victims and to increase their chance of survival, potentially effective drugs and corresponding dosages need to be assessed. For this study, we evaluated the pharmacokinetic and pharmacodynamic properties of enrofloxacin in combination with carprofen, administered to immobilised rhinoceros. From the pharmacokinetic evaluation, intravenous enrofloxacin (12.5 mg/kg) was characterised by an AUC, Cl and t1/2 (Gmean ± SD) of 64.5 ± 14.44 μg*h/mL, 0.19 ± 0.04 L/h*kg and 12.41 ± 2.62 hours, respectively. Of these, the unexpected finding was the extremely long half-life of elimination, which was significantly longer than that of the horse and of any other mammalian species. Subsequent pharmacodynamics modelling showed that daily intravenous application could be useful and could be achieved by means of a light butorphanol sedation, followed by the enrofloxacin administration through an indwelling catheter. To further evaluate if the intravenous priming dose could be maintained by subsequent oral dosing, animals in phase two of the study were treated with a second dose of enrofloxacin in the feed following immobilisation. The oral treatment was deemed inappropriate, as the oral bioavailability of 33.30 ± 38.33% was surprisingly low. Intramuscular carprofen (1 mg/kg), was characterised by an AUC, Cl and t1/2 of 904.61 ± 110.78 μg*h/ml, 0.0011 ± 0.0001 L/h*kg and 105.71 ± 15.67 hours, respectively. As for enrofloxacin, the major finding was the considerably long half-life, which was the longest reported in any species this far. Based on the changes in plasma thromboxane concentration, we surmise that the drug would have an anti-inflammatory effect for a minimum of 48 hours. To gain a better understanding of the prolonged half-life of elimination, two in silico studies were undertaken. For the first study, allometric pharmacokinetic modelling was conducted with enrofloxacin to ascertain if the slower metabolism evident in the rhino could be attributed to the size of the species. Despite the goodness of fit of different models, none were predictive of the actual pharmacokinetic parameters. This leads to the conclusion that the slower metabolism resulted from metabolic constraints as opposed to size-related slower metabolism. To provide insight into the metabolic constrains in the rhino and to ascertain if the rhino genome coded for the enzymes described in the horse, a species closest related to the rhinoceros, the published rhino genome was evaluated using BLAST algorithms. The white rhino nucleotide sequences were 90.74% identical to the equine sequences, which represents the highest degree of similarity amongst all evaluated species sequences. Even though all CYP450 families present in the horse coud be identified in the white rhino, the horse genome contained additional gene sequences for a larger number of iso-enzymes, which were not present in the rhino. Thus, the difference in the metabolic capacity cannot be directly attributed to an absolute deficiency of a CYP enzyme family. However, with the difference possibly being the absence of specific isoenzymes in the rhino, this could suggest that the horse is a more efficient metabolizer. Based on the results of this study, we believe that carprofen shows good promise as an analgesic for use in rhinoceros. While enrofloxacin should be effective, its use is rather limited due to the frequently required intravenous administration. The subsequent in silico modelling suggested that the rhino may exhibit metabolic constraints, which may result from their lower number of isoenzymes. The latter assumption does however require further evaluation.